Plano de ensino individualizado no contexto da educação física escolar - Pereira, Taylor Brian Lavinscky (2018)
Since physical education is a mandatory curricular component of basic education, it has great potential to provide opportunities for inclusion of students with disabilities. However, many Physical Education teachers complain about the lack of knowledge in the area and scarcity of support resources that can assist in their planning. The Individualized Education Plan applied to Physical Education (IEP-PE) consists of a document developed as a guide or action plan for teachers about the different needs of each student with a disability. The general objective of this study was to analyze the construction process and applicability of the Individualized Education Plan in the context of Physical Education under a collaborative perspective and determine its consequences in the pedagogical process. The specific objectives were: to analyze the IEP-PE as a pedagogical strategy in the process of inclusion of students with disabilities in General Physical Education; to identify the possibilities and limitations of the IEP-PE according to the physical education teacher and analyze a participation of students with disabilities in physical education classes before and after the use of the IEP-PE. Under a qualitative approach, the present research was characterized as a collaborative study. The study was developed at two schools from the Regular School Network in a medium-sized city in São Paulo State. The participants were: two physical education teachers linked to the State Education Network, three students with disabilities and their respective parents/guardians. Data was collected through systematic observation and semi-structured interviews to gather information to complete the IEP-PE and for subsequent analysis. Data processing was based on categorical content analysis. The categories were defined from the themes observed in the teachers' responses and in the observation scripts. The results suggest that the IEP-PE can be used as a pedagogical strategy that allows the Physical Education teacher to understand the limitations and abilities of their student, as well as to adjust and adapt their curriculum and pedagogical practices, favoring the inclusion of students with disabilities in school Physical Education classes.